Nature Through Young Eyes: Exploring Children’s Understanding of Nature in Urban Landscapes in Beijing, China - Jianjiao Liu; Raymond James Green (Land)
Rapid urbanization over the last few decades has resulted in children growing up in cities increasingly disconnected from the natural world. A better understanding of children’s conceptions of nature in cities is needed to try to address this unfortunate trend. This study was conducted within four core districts of Beijing, China, and involved interviewing 81 children aged 8 to 12 years to explore their general, conceptual understanding of nature and accessible nature and how it manifests in their daily lives. Some of these children (N = 54) were involved in a follow-up photo Q-sort task aimed at investigating their perceptions of nature in the city, which required them to sort 33 stimuli photographs in piles according to their perceived “naturalness”. The interview data were content analyzed, while the photo-sorting data were subjected to various statistical analyses, including Multidimensional Scaling (MDS). These analyses identified three distinct ways children perceive nature in the city, reflecting ecological, emotional, and visual values for nature in the city. The findings highlight the influence of personal experiences, education, the media, and evolutional predispositions on children’s constructs of nature. The findings can guide environmental design and education actions aimed at integrating nature in urban settings that align better with the children’s conceptions of nature.